The matrix matters, but how should we manage it? Estimating the amount of high‐quality matrix required to maintain biodiversity in fragmented landscapes. Issue 1 (8th June 2016) - Ruffell, Jay; Clout, Mick N.; Didham, Raphael K.
Abstract : Improving matrix quality may be a powerful strategy for conserving biodiversity in fragmented landscapes, but effectively implementing this strategy requires a better understanding of how much of the matrix needs to be converted to 'high‐quality' land uses to achieve conservation goals. Here, we use data on the distribution of forest birds across > 1000 landscapes throughout New Zealand to quantify how the impacts of habitat loss (declining native forest cover) change as the proportion of matrix that is a high‐quality land use (exotic plantation forest) increases. As expected, we found that the amount of plantation forest in the matrix strongly influenced the extent to which native forest loss impacted bird communities: a decline in native forest cover from 90 to 1% caused a 60% decrease in bird species richness when there was no plantation forest in the matrix, but only a 15% decrease when 99% of the matrix was plantation forest. However, this plantation forest effect was strongly nonlinear, with most of the benefits of increasing plantation forest cover occurring before plantations reached even 10% of the matrix. Conversely, increasing plantation forest cover had minimal effects when the matrix was already dominated by plantation forest, or when native forest cover was high. Previous research has confirmed that matrix quality can strongly influence the biodiversity of fragmented landscapes, but results from our study system suggest that managing the matrix to benefit biodiversity could be surprisingly straightforward. Most of these benefits may be achieved by maintaining a small proportion of the matrix as high‐quality land uses.